2018
DOI: 10.1007/s11199-018-0974-9
|View full text |Cite
|
Sign up to set email alerts
|

Reducing a Male Bias in Language? Establishing the Efficiency of Three Different Gender-Fair Language Strategies

Abstract: Different strategies of gender-fair language have been applied to reduce a male bias, which means the implicit belief that a word describing an undefined person describes a man. This male bias might be caused by the words themselves in terms of generic masculine or masculine forms or by androcentrism (the conflation of men with humanity). In two experiments, we tested how different gender-fair strategies used as labels of an unknown social target (an applicant in a recruitment situation) could eliminate the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 37 publications
4
63
0
2
Order By: Relevance
“…Here, research has primarily focused on androcentric versus gender-fair language (e.g., replacing the generic masculine "he" with "he or she") without distinguishing between multi-gendering and de-gendering languages. Findings from this literature show that language has powerful effects both on who comes to mind when using differently gendered terms (Lindqvist et al, 2019) and also how individuals described in gender-fair language are perceived (Budziszewska et al, 2014). It would be interesting to examine such effects by focusing on de-gendering (e.g., replacing "he or she" with "they") and multi-gendering (e.g., replacing "he or she" with "he, she, or ze") strategies to make language more gender-fair.…”
Section: Discussionmentioning
confidence: 99%
“…Here, research has primarily focused on androcentric versus gender-fair language (e.g., replacing the generic masculine "he" with "he or she") without distinguishing between multi-gendering and de-gendering languages. Findings from this literature show that language has powerful effects both on who comes to mind when using differently gendered terms (Lindqvist et al, 2019) and also how individuals described in gender-fair language are perceived (Budziszewska et al, 2014). It would be interesting to examine such effects by focusing on de-gendering (e.g., replacing "he or she" with "they") and multi-gendering (e.g., replacing "he or she" with "he, she, or ze") strategies to make language more gender-fair.…”
Section: Discussionmentioning
confidence: 99%
“…The Swedish word kön (sex) signifies both the biological and social sex and does not refer to sexual practices, as the equivalent English word does (Liinason, 2011). To reduce the male bias in language, where the implicit belief is that a word describing an undefined person describes a man, a third-person gender-neutral pronoun singular (hen) has been introduced in the Swedish language (Lindqvist et al, 2019). Without disregarding recent productions of gender, the concepts "man" and "woman" where in the present study found to be useful analytic tools, especially motivated by the gender-imbalance in previous research on non-heterosexuals online.…”
Section: The Non-heterosexual Online Dating Scenementioning
confidence: 91%
“…It seems to be viewed as truly gender-neutral. When participants in a recent study were asked to remember the gender/sex of a person whose gender/ sex was not disclosed but who was described as either "the applicant" or as hen, most participants indicated that they had read about a man when they had read about "the applicant," but this androcentric bias was not present for hen (Lindqvist et al, 2019). Thus, both performance-based and context-based gender trouble can indeed lead to positive changes and, hopefully, over time, weaken the gender/sex binary.…”
Section: The Positive Effects Of Gender Troublementioning
confidence: 99%